Narratives of change: How Sungai Watch educates on waste management through Instagram - Pratiwi, Aprilianti; Ibtihal, Indi Azzahra (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
The waste problem in Indonesia continues to persist due to the increasing volume of unmanageable waste year by year. The government cannot work alone. The help of social change actors is needed to address the waste issue. Social media has become a platform used for environmental education campaigns, including waste management. This study aims to analyze the narrative of change conveyed by Sungai Watch through educational videos on Instagram. The study uses a qualitative method with a narrative approach to understand the structure and messages contained in the uploaded content. Data were collected through digital observation of the @sungaiwatch account and documentation of six featured videos: Sachets, Plastic Pollution, Easily Cut Down on Single-Use Plastics, Diapers, Trash-Free Muncar Beach, and Empowering the Next Generation. The analysis shows that each video has a narrative structure involving the introduction of the problem, conflict, climax, and resolution, as well as a variety of characters, including the main character Gary Bencheghib, the founder of Sungai Watch, local communities, and the younger generation. The moral message conveyed consistently emphasizes the importance of community collaboration, environmental education, and behavioral change in waste management. The study found that narratives based on real action and practical solutions packaged in visually appealing ways are effective in raising awareness and engaging the audience on waste management issues. This research contributes to the understanding of digital environmental communication, specifically how narratives in social media can be used as an effective educational tool. The findings are relevant for environmental practitioners, academics, and organizations focused on behavior change campaigns related to environmental issues.